THE IMPACT OF CURRENT RATIO, DEBT TO EQUITY RATIO AND RETURN ON EQUITY TOWARDS FIRM VALUE ON CONSUMER GOODS INDUSTRY LISTED ON THE INDONESIA STOCK EXCHANGE - Melina Kosasih; Elizabeth Maria (Journal of Accounting and Management Innovation, 2022)
A company should be able to compile and report its finances for a specific period since it serves as the benchmark for measuring the performance of a company in accordance with its goals and objectives that will reflect the achievement and ability of the company to operate its business financially. Firm value will reflect the overall performance of a company in which it becomes one of the things that the investors will pay attention to before making an investment decision. In this research, a firm value is being measured by using the Tobin’s Q ratio. The purpose of this research is to determine the impact of Current Ratio, Debt to Equity Ratio and Return on Equity towards Firm Value on consumer goods industry listed on the Indonesia Stock Exchange. Using the purposive sampling method, out of a total population of 46 companies, 29 companies were selected as sample. The analysis model used in this research is the multiple linear regression model using IBM SPSS Statistics 25.0. The results of this research indicate that partially, Current Ratio has an insignificant negative impact towards Firm Value, Debt to Equity Ratio has an insignificant negative impact towards Firm Value, and Return on Equity has a significant positive impact towards Firm Value. Simultaneously, Current Ratio, Debt to Equity Ratio and Return on Equity have a significant impact towards Firm Value.